FINANCIAL DISTRESS, LEVERAGE, TENURE AUDITS, AND COMPANY SIZE AGAINST REPORT INTEGRITY FINANCE IN STATE-OWNED COMPANIES THAT LISTED ON THE INDONESIA STOCK EXCHANGE - Saraswati, Wiwik; Karlinda , Dika; Lestari, Winda (MEDIA RISET EKONOMI [MR.EKO], 2025)
The purpose of this study is to determine the influence of financial distress, leverage, audit tenure, and company size on the integrity of financial statements. The data used in this study is secondary data on State-Owned Enterprises (SOEs) for the 2022-2024 period. The data collection technique uses the purposive sampling method. The data analysis method uses multiple linear regression. The results of the analysis show that financial distress has no effect on the integrity of financial statements. Tenure audits have no effect on the integrity of financial statements. The size of the company has no effect on the integrity of the financial statements. Meanwhile, leverage affects the integrity of financial statements.